2018
DOI: 10.1021/acsami.8b08851
|View full text |Cite
|
Sign up to set email alerts
|

Shape Memory Ankle–Foot Orthoses

Abstract: Electrically actuated ankle-foot orthoses (AFOs) were designed and prototyped using shape memory textile composites. Acrylic copolymers were synthesized as the matrix to demonstrate shape memory effects, whereas electrothermal fabrics were embedded to generate uniform heat as a trigger. Superior to conventional polymeric orthoses, shape memory AFOs (SM-AFOs) could be repeatedly programmed at least 20 times with stable shape fixity and recovery. Evidenced by clinical practice, SM-AFOs were effectively actuated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 36 publications
0
21
0
Order By: Relevance
“…For the realization of wearable electronics, an important trend in the last years has been incorporating electroactive nanomaterials with commercial textiles . Many pioneer works has shown that is possible to modify such textiles and its applications span over a wide range of fields, including wearable supercapacitors, electrical sensors, health monitoring devices, energy storage and conversion devices, artificial intelligence, smart textiles, and numerous others . In terms of electroactive materials, polypyrrole, gold nanowires, carbon nanotubes graphene, carbon‐based materials have been supposed to be the good candidates for fabrication of wearable electronic textiles owing to its lightness, excellent mechanical properties, and high conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…For the realization of wearable electronics, an important trend in the last years has been incorporating electroactive nanomaterials with commercial textiles . Many pioneer works has shown that is possible to modify such textiles and its applications span over a wide range of fields, including wearable supercapacitors, electrical sensors, health monitoring devices, energy storage and conversion devices, artificial intelligence, smart textiles, and numerous others . In terms of electroactive materials, polypyrrole, gold nanowires, carbon nanotubes graphene, carbon‐based materials have been supposed to be the good candidates for fabrication of wearable electronic textiles owing to its lightness, excellent mechanical properties, and high conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…The first‐level micropillars are primarily hexagon with diameter, height and channel width of about 10, 5, and 0.5 µm (Figure 1b,c). [ 26 ] The second‐level hexagonal nanopillars have a diameter of ≈250 nm (Figure 1d,e), and nanoscale cavity with depth of ≈20 nm is on top (Figure 1f). Inspired by tree frog's structural features, various bioinspired pillar surfaces have been fabricated with polydimethylsiloxane (PDMS) to study the interfacial liquid behavior and its effects, including single‐level pillar surface, hierarchical pillar surface and hierarchical concave pillar surface (Figure 1h,i; Figures S1 and S2 and Table S1, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…[ 98 ] incorporated cellulose nanowhiskers into the PU network, with both temperature and water applied to trigger shape recovery of the copolymer. Chen and co‐workers [ 254 ] designed a smart orthopedic system that was expected to drop foot therapy. Here, a conductive acrylate‐based copolymer was fabricated with silver coating nylon yarns by full Milano stitching.…”
Section: Recent Advances In Applications Of Smps and Smpcsmentioning
confidence: 99%